(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Knowledge management, learning methods, academic performance. In times of the second pandemic outbreak, the influence of knowledge management in the area of communication on the development of teaching competencies at the Julcán-2021 Educational Institution was determined. La Libertad, Peru. The study corresponds to a non-experimental, descriptive correlational causal design. A population equal to the sample of 73 teachers was reported, chosen by means of a non-probabilistic, intentional and directed sample selection. The information collection instrument was the survey to determine the levels of knowledge management in teachers by (Velásquez, 2018), which evaluates the dimensions: Organizational culture, internal communication, competency development and planning. To measure the levels of teaching competencies elaborated by (Rivilla et al. 2013), which evaluates the dimensions: methodological, social, personal and technical. For the association, the Rho Spearman coefficient was used and for the effect the linear regression, registering: knowledge management and its dimensions, significantly (p<0.01) influence teaching competencies (r= 0.935, r2 = 87.4%; r=0, 761, r2 = 57.9%; r=0.754, r2 = 56.8%; r=0.849, r2 = 72.1%; r= 0.706, r2 = 49.8%). In conclusion, the predictive model of knowledge management has an 87.4% influence on teaching competencies. Knowledge management and its elements should be stimulated to increase teaching competencies in the Julcán-2021 educational institution.